Use of Tissue Culture Techniques for Producing Virus-Free Plant in Garlic and Their Identification through Real-Time PCR. (7th July 2013) - Taşkın, Hatıra; Baktemur, Gökhan; Kurul, Mehmet; Büyükalaca, Saadet
Abstract : This study was performed for comparison of meristem culture technique with shoot tip culture technique for obtaining virus-free plant, comparison of micropropagation success of two different nutrient media, and determination of effectiveness of real-time PCR assay for the detection of viruses. Two different garlic species ( Allium sativum and Allium tuncelianum ) and two different nutrient media were used in this experiment. Results showed that Medium 2 was more successful compared to Medium 1 for both A. tuncelianum and A. sativum (Kastamonu garlic clone). In vitro plants obtained via meristem and shoot tip cultures were tested for determination of onion yellow dwarf virus (OYDV) and leek yellow stripe virus (LYSV) through real-time PCR assay. In garlic plants propagated via meristem culture, we could not detect any virus. OYDV and LYSV viruses were detected in plants obtained via shoot tip culture. OYDV virus was observed in amount of 80% and 73% of tested plants for A. tuncelianum and A. sativum, respectively. LYSV virus was found in amount of 67% of tested plants of A. tuncelianum and in amount of 87% of tested plants of A. sativum in this study.